Desenvolvimento de um sistema de medição para análise da força de arrasto em torno de um cilindro - Soares, Camilo da Silva (2021)
Drag is one of the main objects of study in aerodynamics, its control is directly associated with the improvement of cars, planes or any other object that interacts with a moving fluid. The purpose of this work was to develop a system capable of determining the drag force and the drag coefficient of a cylinder inside of a didactic wind tunnel. For that, it was necessary to design and build a data capture mechanism based on the use of strain gauges and an amplifier module HX711 controlled by an Arduino UNO board. The validation of the experiment was done by comparing the result of the drag coefficient obtained by the projected system with the drag coefficient obtained by literature. The data captured by the designed mechanism corroborate the literature presented and the system can be used for research purposes, as well as in experimental classes in the Fluid Mechanics discipline of the Mechanical Engineering course at the Federal University of Rio Grande do Norte.